A method for preparing an axially chloro-coordinated high-loading metal monatomic catalyst
Patent Information
- Application Number
- CN202611171188.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]然而,目前高负载量且结构明确的轴向氯配位单原子催化剂的制备仍面临重大挑战
1、本发明采用两次球磨法,首先使聚合物前驱体与金属自聚,锚定大量的金属离子,随后加入氮源发生共聚,进一步锚定剩余金属离子,且采用氯盐作为氯配位原料,原位形成氯配位结构。
Smart Images

Figure CN122875223A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing catalysts, specifically to a method for preparing axially chlorine-coordinated, highly loaded metal single-atom catalysts using a polymer anchoring strategy. Background Technology
[0002] Single-atom catalysts (SACs) exhibit exceptional activity and selectivity in catalysis due to their extremely high atom utilization and unique electronic structure, serving as a bridge between heterogeneous and multiphase catalysis. Among numerous SACs, precise control of the local coordination environment of the metal active center, especially the introduction of axial ligands, has become a key strategy for optimizing their electronic properties and enhancing specific catalytic performance. Chloride ions, as a typical axial ligand, can effectively modulate the d-orbital energy levels and charge distribution of the central metal atom, thereby affecting its activity and stability in redox reactions, organic synthesis, and electrocatalysis.
[0003] However, the preparation of highly loaded and structurally well-defined axially coordinated single-atom catalysts still faces significant challenges. Traditional preparation methods, such as impregnation and co-precipitation, often fail to simultaneously achieve high-density, uniform dispersion of metal atoms on the support and controllable construction of the axial coordination structure. At lower loading levels, while isolated atoms may be obtained, the overall catalyst activity is limited; conversely, when pursuing high loading levels, metal atoms readily migrate and aggregate to form nanoparticles, leading to the loss of single-atom properties. Furthermore, the pre-designed axially coordinated structure is easily disrupted during heat treatment or reaction processes, making it difficult to maintain stability.
[0004] To address the aforementioned issues, various stabilization strategies have been developed in recent years, among which polymer-assisted or anchoring strategies have shown unique advantages. Certain polymers rich in nitrogen and oxygen coordinating atoms (such as polydopamine and polyethyleneimine) can form strong interactions with metal precursors through their functional groups, effectively restricting the migration of metal atoms during pyrolysis and promoting the formation and stabilization of single-atom sites. However, how to utilize such strategies to achieve high metal loading while simultaneously introducing and stabilizing chlorine ligands at the axial positions of metal atoms to form a well-defined and stable N4-M-Cl coordination structure remains a pressing technical challenge in this field.
[0005] Therefore, developing a new method for preparing axially chlorine-coordinated, highly loaded metal single-atom catalysts is of great theoretical and practical significance for a deeper understanding of the influence mechanism of coordination environment on single-atom catalytic performance and for promoting their efficient application in energy, chemical engineering, environmental protection and other fields. Summary of the Invention
[0006] In view of the problems existing in the prior art, the present invention aims to provide a preparation method based on a polymer anchoring strategy to overcome the shortcomings of the prior art. This method is expected to achieve uniform and high-density anchoring of the metal precursor on the support surface, and through controllable heat treatment and post-treatment processes, to successfully construct and stabilize the axial chlorine coordination structure of the metal center while obtaining a high-loading single-atom catalyst, thus providing a new technical approach for the design and preparation of high-performance single-atom catalysts.
[0007] A method for preparing axially chlorine-coordinated highly supported metal single-atom catalysts using a polymer anchoring strategy, characterized by comprising the following steps: (1) The polymer precursor was mixed with hydrated metal chloride salt, and the mixture was transferred into a ball mill jar for ball milling to obtain a polymer-metal self-polymerized composite precursor. (2) Add a suitable nitrogen source to the composite precursor obtained in step (1), and transfer the above mixture into a ball mill jar for ball milling to obtain a polymer copolymer metal composite precursor.
[0008] (3) The mixture obtained in step (2) is transferred to a ceramic boat and calcined at high temperature under inert gas protection in a tube furnace. It is then naturally cooled to room temperature to obtain a highly loaded metal single-atom catalyst with axial chlorine coordination.
[0009] Preferably, the polymer precursor in step (1) is one of dopamine hydrochloride, levodopa, catechol, 3,4-dihydroxybenzonitrile, 3,4-dihydroxyphenylacetic acid, 3,4-dihydroxybenzaldehyde, dobutamine and gallic acid.
[0010] Preferably, the ball milling time in step (1) is 2-5 h and the rotation speed is 300-600 rpm.
[0011] Preferably, the hydrated metal salt mentioned in step (1) is one of ferric chloride hexahydrate, copper chloride hexahydrate, cobalt chloride hexahydrate, chromium chloride hexahydrate, nickel chloride hexahydrate, aluminum chloride hexahydrate, aluminum chloride hexahydrate, copper chloride dihydrate, and tin chloride dihydrate.
[0012] Preferably, the nitrogen source in step (2) is one of polyethyleneimine, urea, melamine, triethylenediamine, ethylenediamine, polyacrylamide, chitosan, cyclohexylamine and dicyandiamide.
[0013] Preferably, the ball milling time in step (2) is 2-5 h, and the rotation speed is 300-600 rpm. The mass ratio of the milling beads to the sample is 1:25-1:100.
[0014] Preferably, the inert gas in step (3) is one or two of nitrogen, argon and helium.
[0015] Preferably, the conditions in step (3) are to heat to 200-400 ℃ at a heating rate of 2-10 ℃ / min and hold for 1-4 h, and then heat to 500-700 ℃ at a heating rate of 2-10 ℃ / min and hold for 1-4 h.
[0016] Compared with the prior art, the present invention has the following advantages: 1. The present invention employs a two-stage ball milling method. First, the polymer precursor and the metal self-polymerize to anchor a large number of metal ions. Then, a nitrogen source is added to cause copolymerization, further anchoring the remaining metal ions. Furthermore, chloride salts are used as chloride coordination raw materials to form chloride coordination structures in situ.
[0017] 2. The metal loading of the axially chlorine-coordinated high-load metal single-atom catalyst of the present invention can reach 25 wt%, which shows a high loading.
[0018] 3. The high-loaded metal single-atom catalyst with axial chlorine coordination of the present invention has a simple preparation process, simple reaction equipment, low production cost and high safety, and broad market prospects. Attached Figure Description
[0019] Figure 1 The image shows the XRD pattern of the axially chlorine-coordinated highly loaded metal single-atom catalyst prepared in Example 1. Figure 2 SEM images of the axially chlorine-coordinated highly loaded metal single-atom catalyst prepared in Example 1 at different folds; Figure 3 Aberration-corrected transmission electron microscope image of the axially chlorine-coordinated highly loaded metal single-atom catalyst prepared in Example 1; Figure 4 TEM image of the axially chlorine-coordinated highly loaded metal single-atom catalyst prepared in Example 1; Figure 5 TEM image of the highly loaded nanoparticle metal catalyst prepared for Comparative Example 1.
[0020] Figure 6 TEM image of the highly loaded nanoparticle metal catalyst prepared for Comparative Example 2. Detailed Implementation
[0021] The present invention will be further described below with reference to the accompanying drawings and embodiments, but the scope of protection of the present invention is not limited to the scope described.
[0022] Example 1: Weigh 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.47 g of dopamine hydrochloride and place them in a ball mill jar. The ball milling conditions are 400 rpm for 2 h. After the reaction is complete, the Fe-PDA polymer precursor is obtained.
[0023] Subsequently, 0.93 g of polyethyleneimine (PEI) and 0.1 g of dicyandiamide were added to the Fe-PDA polymer precursor and ball milling was continued at 400 rpm for 2 h. After the reaction was completed, the Fe-CN polymer precursor was obtained.
[0024] The Fe-CN polymer precursor obtained in step (2) was transferred to a ceramic boat. Under argon protection in a tube furnace, the temperature was first raised to 400 ℃ at a heating rate of 5 ℃ / min and held for 3 h. Then, the temperature was raised to 600 ℃ at a heating rate of 5 ℃ / min and held for 3 h. The catalyst was then naturally cooled to room temperature to obtain an axially chlorine-coordinated high-load metal single-atom catalyst with an iron loading of 25.5 wt%.
[0025] The XRD pattern of the axially chlorine-coordinated highly supported metal single-atom catalyst prepared in this embodiment is shown in the figure below. Figure 1 As shown, there are no obvious metallic characteristic peaks, indicating that there are no metal nanoparticles or clusters in the material.
[0026] The SEM image of the axially chlorine-coordinated highly supported metal single-atom catalyst prepared in this embodiment is shown below. Figure 2 As shown, the catalyst exhibits a plate-like structure.
[0027] Aberration-corrected transmission electron microscope image of the axially chlorine-coordinated highly supported metal single-atom catalyst prepared in this embodiment is shown below. Figure 3 As shown, there are no clustered bright spots, proving that the metal exists at the atomic level.
[0028] TEM image of the axially chlorine-coordinated highly supported metal single-atom catalyst prepared in this embodiment is shown below. Figure 4 As shown, there are no obvious zebra stripes, indicating that there are no nanoparticles or clusters in the material.
[0029] Example 2: (1) Weigh 1.19 g of cobalt chloride hexahydrate (CoCl2·6H2O) and 0.47 g of dopamine hydrochloride (DA) and put them into a ball mill jar. The ball milling conditions are 500 rpm and 3 h. After the reaction is completed, the Co-PDA polymer precursor is obtained.
[0030] (2) Subsequently, 0.93 g of polyethyleneimine (PEI) and 0.23 g of polyacrylamide were added to the Co-PDA polymer precursor and ball milling was continued at 500 rpm for 3 h. After the reaction was completed, the Co-CN polymer precursor was obtained.
[0031] (3) The Co-CN polymer precursor obtained in step (2) was transferred to a ceramic boat. Under argon protection in a tube furnace, the temperature was first increased to 350 °C at a rate of 8 °C / min and held for 2 h. Then, the temperature was increased to 700 °C at a rate of 8 °C / min and held for 2 h. The mixture was then naturally cooled to room temperature to obtain an axially chlorine-coordinated high-load metal single-atom catalyst with a cobalt loading of 26.2 wt%. The metal dispersion on the matrix was similar to... Figure 3 resemblance.
[0032] Example 3: (1) Weigh 1.19 g of nickel chloride hexahydrate (NiCl2·6H2O) and 0.55 g of catechol and put them into a ball mill jar. The ball milling conditions are 300 rpm and 1 h. After the reaction is completed, the Ni-PDA polymer precursor is obtained.
[0033] (2) Subsequently, 0.93 g of polyethyleneimine (PEI) and 0.1 g of dicyandiamide were added to the Ni-PDA polymer precursor and ball milling was continued at 300 rpm for 1 h. After the reaction was completed, the Ni-CN polymer precursor was obtained.
[0034] (3) The Ni-CN polymer precursor obtained in step (2) was transferred to a ceramic boat. Under argon protection in a tube furnace, the temperature was first increased to 300 °C at a rate of 4 °C / min and held for 4 h. Then, the temperature was increased to 500 °C at a rate of 4 °C / min and held for 4 h. The mixture was then naturally cooled to room temperature to obtain a highly loaded metal single-atom catalyst with axial chlorine coordination. The nickel loading was 24.8 wt%. The metal dispersion on the matrix was similar to... Figure 3 resemblance.
[0035] Example 4: (1) Weigh 1.19 g of chromium chloride hexahydrate (CrCl3·6H2O) and 0.45 g of 3,4-dihydroxyphenylacetic acid and place them in a ball mill jar. The ball milling conditions are 500 rpm and 1 h. After the reaction is complete, the Cr-PDA polymer precursor is obtained.
[0036] (2) Subsequently, 0.93 g of polyethyleneimine (PEI) and 0.1 g of dicyandiamide were added to the Cr-PDA polymer precursor and ball milling was continued at 500 rpm for 1 h. After the reaction was completed, the Cr-CN polymer precursor was obtained.
[0037] (3) The Cr-CN polymer precursor obtained in step (2) was transferred to a ceramic boat. Under argon protection in a tube furnace, the temperature was first increased to 400 ℃ at a rate of 2 ℃ / min and held for 4 h. Then, the temperature was increased to 600 ℃ at a rate of 2 ℃ / min and held for 4 h. The mixture was then naturally cooled to room temperature to obtain an axially chlorine-coordinated high-load metal single-atom catalyst with a chromium loading of 24.4 wt%. The metal dispersion on the matrix was similar to... Figure 3 resemblance.
[0038] Example 5: (1) Weigh 0.85 g of copper chloride dihydrate (CuCl2·2H2O) and 0.47 g of dopamine hydrochloride (DA) and put them into a ball mill jar. The ball milling conditions are 600 rpm and 5 h. After the reaction is completed, the Cu-PDA polymer precursor is obtained.
[0039] (2) Subsequently, 1.86 g of polyethyleneimine (PEI) and 0.2 g of dicyandiamide were added to the Cu-PDA polymer precursor and ball milling was continued at 600 rpm for 2 h. After the reaction was completed, the Cu-CN polymer precursor was obtained.
[0040] (3) The Cu-CN polymer precursor obtained in step (2) was transferred to a ceramic boat. Under argon protection in a tube furnace, the temperature was first increased to 400 °C at a rate of 10 °C / min and held for 1 h. Then, the temperature was increased to 700 °C at a rate of 10 °C / min and held for 1 h. The mixture was then naturally cooled to room temperature to obtain a highly loaded metal single-atom catalyst with axially coordinated chlorine. The Cu loading was 23.9 wt%. The metal dispersion on the matrix was similar to... Figure 3 resemblance.
[0041] Example 6: (1) Weigh 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.52 g of 3,4-dihydroxybenzaldehyde and place them in a ball mill jar. The ball milling conditions are 600 rpm for 5 h. After the reaction is complete, the Fe-PDA polymer precursor is obtained.
[0042] (2) Subsequently, 1.2 g of melamine and 0.1 g of dicyandiamide were added to the Fe-PDA polymer precursor and ball milling was continued at 600 rpm for 5 h. After the reaction was completed, the Fe-CN polymer precursor was obtained.
[0043] (3) The Fe-CN polymer precursor obtained in step (2) was transferred to a ceramic boat. Under argon protection in a tube furnace, the temperature was first increased to 300 °C at a rate of 3 °C / min and held for 2 h. Then, the temperature was increased to 500 °C at a rate of 3 °C / min and held for 4 h. The mixture was then naturally cooled to room temperature to obtain an axially chlorine-coordinated high-load metal single-atom catalyst with an iron loading of 25.1 wt%. The metal dispersion on the matrix was similar to... Figure 3 resemblance.
[0044] Example 7: (1) Weigh 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.47 g of dopamine hydrochloride (DA) and put them into a ball mill jar. The ball milling conditions are 300 rpm and 5 h. After the reaction is completed, the Fe-PDA polymer precursor is obtained.
[0045] (2) Subsequently, 0.93 g of polyethyleneimine (PEI) and 0.2 g of urea were added to the Fe-PDA polymer precursor and ball milling was continued at 300 rpm for 5 h. After the reaction was completed, the Fe-CN polymer precursor was obtained.
[0046] (3) The Fe-CN polymer precursor obtained in step (2) was transferred to a ceramic boat. Under argon protection in a tube furnace, the temperature was first increased to 200 °C at a rate of 8 °C / min and held for 4 h. Then, the temperature was increased to 700 °C at a rate of 8 °C / min and held for 4 h. The mixture was then naturally cooled to room temperature to obtain an axially chlorine-coordinated high-load metal single-atom catalyst with an iron loading of 21.3 wt%. The metal dispersion on the matrix was similar to... Figure 3 resemblance.
[0047] Example 8: (1) Weigh 0.675 g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.47 g of dopamine hydrochloride (DA) and put them into a ball mill jar. The ball milling conditions are 500 rpm and 2 h. After the reaction is completed, the Fe-PDA polymer precursor is obtained.
[0048] (2) Subsequently, 1.2 g of melamine and 0.2 g of urea were added to the Fe-PDA polymer precursor and ball milling was continued at 500 rpm for 2 h. After the reaction was completed, the Fe-CN polymer precursor was obtained.
[0049] (3) The Fe-CN polymer precursor obtained in step (2) was transferred to a ceramic boat. Under argon protection in a tube furnace, the temperature was first increased to 400 °C at a rate of 4 °C / min and held for 1 h. Then, the temperature was increased to 600 °C at a rate of 4 °C / min and held for 1 h. The mixture was then naturally cooled to room temperature to obtain an axially chlorine-coordinated high-load metal single-atom catalyst with an iron loading of 11.7 wt%. The metal dispersion on the matrix was similar to... Figure 3 resemblance.
[0050] Example 9: (1) Weigh 2.025 g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.47 g of dopamine hydrochloride (DA) and put them into a ball mill jar. The ball milling conditions are 300 rpm and 5 h. After the reaction is completed, the Fe-PDA polymer precursor is obtained.
[0051] (2) Subsequently, 0.93 g of polyethyleneimine (PEI) and 0.2 g of dicyandiamide were added to the Fe-PDA polymer precursor and ball milling was continued at 300 rpm for 5 h. After the reaction was completed, the Fe-CN polymer precursor was obtained.
[0052] (3) The Fe-CN polymer precursor obtained in step (2) was transferred to a ceramic boat. Under argon protection in a tube furnace, the temperature was first increased to 200 °C at a rate of 5 °C / min and held for 4 h. Then, the temperature was increased to 700 °C at a rate of 5 °C / min and held for 4 h. The mixture was then naturally cooled to room temperature to obtain a highly loaded metal single-atom catalyst with axial chlorine coordination. The iron loading was 35.2 wt%. The metal dispersion on the matrix was similar to... Figure 3 resemblance.
[0053] Comparative Example 1: (1) Weigh 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.47 g of dopamine hydrochloride (DA) and put them into a ball mill jar. The ball milling conditions are 400 rpm and 2 h. After the reaction is completed, the Fe-PDA polymer precursor is obtained.
[0054] (2) The Fe-PDA polymer precursor obtained in step (1) is transferred to a ceramic boat. Under argon protection in a tube furnace, the temperature is first raised to 400 ℃ at a heating rate of 5 ℃ / min and held for 3 h. Then the temperature is raised to 600 ℃ at a heating rate of 5 ℃ / min and held for 3 h. The material is then naturally cooled to room temperature to obtain a high-loaded nanoparticle metal catalyst.
[0055] SEM images of the highly supported nanoparticle metal catalyst prepared in this comparative example are shown below. Figure 5The iron oxide particles exhibit agglomeration on the matrix surface, indicating that the lack of a second nitrogen source cannot reduce metal dispersion, which is detrimental to the successful preparation of axially coordinated single-atom catalysts.
[0056] Comparative Example 2: (1) Weigh 1.35 g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.93 g of polyethyleneimine (PEI) and place them in a ball mill jar. The ball milling conditions are 400 rpm for 2 h. After the reaction is complete, the Fe-PEI polymer precursor is obtained.
[0057] (2) The Fe-PEI polymer precursor obtained in step (1) was transferred to a ceramic boat. Under the protection of argon in a tube furnace, the temperature was first raised to 400 ℃ at a heating rate of 5 ℃ / min and held for 3 h. Then the temperature was raised to 600 ℃ at a heating rate of 5 ℃ / min and held for 3 h. The temperature was then naturally cooled to room temperature to obtain a high-loaded nanoparticle metal catalyst.
[0058] SEM images of the highly supported nanoparticle metal catalyst prepared in this comparative example are shown below. Figure 6 Ferrous chloride particles agglomerate on the matrix surface, indicating that the lack of a first-step polymer group to anchor the metal is not conducive to metal dispersion and makes it impossible to successfully prepare an axially coordinated single-atom catalyst.
Claims
1. A method for preparing a highly supported metal single-atom catalyst with axial chlorine coordination, characterized in that, Includes the following steps: (1) The polymer precursor was mixed with hydrated metal chloride salt, and the mixture was transferred into a ball mill jar for ball milling to obtain a polymer-metal self-polymerized composite precursor. (2) Add a suitable nitrogen source to the composite precursor obtained in step (1), and transfer the above mixture into a ball mill jar for ball milling to obtain a polymer copolymer metal composite precursor; (3) The mixture obtained in step (2) is transferred to a ceramic boat and calcined at high temperature under inert gas protection in a tube furnace. It is then naturally cooled to room temperature to obtain a highly loaded metal single-atom catalyst with axial chlorine coordination.
2. The method for preparing an axially chlorine-coordinated highly supported metal single-atom catalyst according to claim 1, characterized in that, The polymer precursor mentioned in step (1) is one of dopamine hydrochloride, levodopa, catechol, 3,4-dihydroxybenzonitrile, 3,4-dihydroxyphenylacetic acid, 3,4-dihydroxybenzaldehyde, dobutamine, or gallic acid.
3. The method for preparing an axially chlorine-coordinated highly supported metal single-atom catalyst according to claim 1, characterized in that, The hydrated metal salt mentioned in step (1) is one of ferric chloride hexahydrate, copper chloride hexahydrate, cobalt chloride hexahydrate, chromium chloride hexahydrate, nickel chloride hexahydrate, aluminum chloride hexahydrate, aluminum chloride hexahydrate, copper chloride dihydrate, or tin chloride dihydrate.
4. The method for preparing an axially chlorine-coordinated highly supported metal single-atom catalyst according to claim 1, characterized in that, The ball milling time in step (1) is 2-5 h, and the rotation speed is 300-600 rpm; wherein, the mass ratio of the ball milling beads to the mixed material used in the ball milling process is 1:25-1:
100.
5. The method for preparing an axially chlorine-coordinated highly supported metal single-atom catalyst according to claim 1, characterized in that, The nitrogen source mentioned in step (2) is one of polyethyleneimine, urea, melamine, triethylenediamine, ethylenediamine, polyacrylamide, chitosan, cyclohexylamine, or dicyandiamide.
6. The method for preparing axially chlorine-coordinated highly loaded metal single-atom catalysts using a polymer anchoring strategy according to claim 1, characterized in that, The ball milling time in step (2) is 2-5 h, and the rotation speed is 300-600 rpm.
7. The method for preparing an axially chlorine-coordinated highly supported metal single-atom catalyst according to claim 1, characterized in that, The inert gas mentioned in step (3) is one or two of nitrogen, argon, or helium; the conditions are to heat to 200-400 ℃ at a heating rate of 2-10 ℃ / min and hold for 1-4 h, and then heat to 500-700 ℃ at a heating rate of 2-10 ℃ / min and hold for 1-4 h.